Playing-Dumb Behavior of Trainers During Online Streaming and Trainee’s Burnout Behavior: Mediating Role of Psychological Disengagement - Xie, Qing; Li, Shidong; Malik, Haider A.; Chupradit, Supat; Chupradit, Priyanut W.; Qadus, Abdul (Frontiers in Psychology, 2022)
Trainer’s behavior is a crucial antecedent to affects the cognitive engagement of trainees in 5 pieces of training and development programs. Conversely, playing dumb behavior by a trainer 6 can cause lower attachment and less interested trainees during the course. In online broadcasting, 7 teachers' playing dumb has a significant impact on trainee burnout. Surprisingly, psychological 8 disengagement plays a big influence in the relationship between trainers and trainees, resulting in 9 considerable performance. Furthermore, the significance of psychological disengagement in 10 mediating between trainers' playing dumb behavior and trainees' burnout behavior during online 11 streaming was explored in this study. Current research follows structural equation modeling 12 (SEM) to model the path relationship among constructs. The study is surveyed based, and data is 13 collected from 372 trainees through a questionnaire. Overall, the out demonstrated that the 14 suggested study model is effective in predicting and measuring the relationship between trainers' 15 dumb behavior and its impact on trainee behavior, which leads to burnout. Furthermore, the role 16 of psychological disengagement as a mediating factor was studied, and it was found to strongly 17 moderate the association between trainers' dumb behavior and trainees' burnout behavior. These 18 findings contribute to the inclusive body of knowledge of playing dumb behavior and trainees’ 19 burnout during the course. The research describes research limitations